Applications of DNA Microsatelite Markers Intilapia Culture - Bhassu, Subha (2002)
In Malaysia, the role of aquaculture in fish production is anticipated to increase as marine fish catches have already exceeded the maximum sustainable yield. In order to address this issue, aquaculture is being developed on a commercial scale. Fish farming in Malaysia is focused on providing the fish grower with the best fingerlings, with uniformity and fast growth rates. There is great necessity for genetic evaluation, monitoring of stocks and application of appropriate breeding approaches if tilapia production is to continue to meet market demands. With the aid of microsatellite markers, stock integrity and genetic variability can be examined. Three major experiments were carried out; a population genetic study on eight populations of tilapia. quantitative genetics study on two populations of O. niloticus. Taiwan A and B across two generations and heritability study on the Taiwan A population. The primary focus of the population genetic study was to determine the relationships among eight populations which was used for breeding and to determine the viability of these populations. Microsatellite markers were used to determine the relationships among tilapia populations. The technique was optimized by varying parameters including the amount of template DNA, different thermal cyclers and others. The results showed that microsatellite markers are good markers for tilapia genetic studies. For the population genetic study, the mean allele number and the mean heterozygosity level for the 40 loci were 43 and 0.5420 respectively. The FST value of 0.2401 among the populations suggested a moderate amount of genetic differentiation among the tilapia populations studied. Low heterozygosity levels suggest low effective population sizes, which may result in high levels ·of inbreeding. Most loci showed a deficiency in heterozygosity, which may be a sign of inbreeding. Most sampled populations showed significant deviations from Hardy-Weinberg equilibrium, which could result from mutation, migration or selection. This outcome could also be due to the small sample sizes examined and the high number of alleles present at individual loci. Based on 11 loci, different genetic distance measures were applied to test the difference in the topology of the five populations examined. The topology and correlation values varied using two models, IAM and SMM. The genetic distances used in this study was selected to resolve relationships among the sampled populations as an